Transcriptomic, metabolomic, and ATAC-seq analysis reveal the regulatory mechanism of senescence of post-harvest tomato fruit - Guo, Susu; Ji, Yanhai; Zheng, Yanyan; Watkins, Christopher B.; Ma, Lili; Wang, Qing; Liang, Hao; Bai, Chunmei; Fu, Anzhen; Li, Ling; Meng, Demei; Liu, Mingchi; et al. (Frontiers in Plant Science, 2023)
Several physiological changes occur during fruit storage, which include the regulation of genes, metabolisms and transcription factors. In this study, we compared ‘JF308’ (a normal tomato cultivar) and ‘YS006’ (a storable tomato cultivar) to determine the difference in accumulated metabolites, gene expression, and accessible chromatin regions through metabolome, transcriptome, and ATAC-seq analysis. A total of 1006 metabolites were identified in two cultivars. During storage time, sugars, alcohols and flavonoids were found to be more abundant in ‘YS006’ compared to ‘JF308’ on day 7, 14, and 21, respectively. Differentially expressed genes, which involved in starch and sucrose biosynthesis were observed higher in ‘YS006’. ‘YS006’ had lower expression levels of CesA (cellulose synthase), PL (pectate lyase), EXPA (expansin) and XTH (xyglucan endoglutransglucosylase/hydrolase) than ‘JF308’. The results showed that phenylpropanoid pathway, carbohydrate metabolism and cell wall metabolism play important roles in prolonging the shelf life of tomato (Solanum lycopersicum) fruit. The ATAC-seq analysis revealed that the most significantly up-regulated transcription factors during storage were TCP 2,3,4,5, and 24 in ‘YS006’ compared to ‘JF308’ on day 21. This information on the molecular regulatory mechanisms and metabolic pathways of post-harvest quality changes in tomato fruit provides a theoretical foundation for slowing post-harvest decay and loss, and has theoretical importance and application value in breeding for longer shelf life cultivars.